THE LEGAL POSITION OF THE SHAREHOLDER IN A PUBLIC JOINT-STOCK COMPANY - Saad Mahdi Salih (American Journals Publishing, 2025)
This study aims to define a clear and comprehensive concept of the legal status of shareholders in a public limited company, detailing their rights and responsibilities. It also seeks to analyze the legal texts regulating this status in the Companies Law and related laws, and demonstrate their clarity and adequacy. Furthermore, the study aims to shed light on the most prominent problems and challenges facing shareholders in exercising their rights, or those that raise confusion about their responsibilities. The study then proposes legal and practical recommendations aimed at enhancing the protection of the legal status of shareholders, improving the mechanisms for exercising rights, and clarifying responsibilities. The most important findings are that legal mechanisms for protecting shareholders, such as invalidity and liability lawsuits, provide a safety net for minority shareholders against the arbitrariness of the majority or mismanagement, thus enhancing the principle of fairness within the company. The most important recommendations include the need to review and simplify judicial procedures related to invalidity and liability lawsuits, reduce the timeframes for adjudicating them, and consider establishing specialized commercial courts. This will enable shareholders to exercise their legal rights more effectively and quickly and deter any illegal practices.
Keywords: Civil liability, public limited joint-stock companies, shareholders, subscription